2017
DOI: 10.1038/srep42492
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive quantification of blood potassium concentration from ECG in hemodialysis patients

Abstract: Blood potassium concentration ([K+]) influences the electrocardiogram (ECG), particularly T-wave morphology. We developed a new method to quantify [K+] from T-wave analysis and tested its clinical applicability on data from dialysis patients, in whom [K+] varies significantly during the therapy. To elucidate the mechanism linking [K+] and T-wave, we also analysed data from long QT syndrome type 2 (LQT2) patients, testing the hypothesis that our method would have underestimated [K+] in these patients. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(79 citation statements)
references
References 37 publications
2
60
0
Order By: Relevance
“…The relationship between this metric and blood plasma potassium concentration suggested that the metric could actually measure outward potassium current. This hypothesis was confirmed by model studies and measurements on LQT2-patients [8]. Incidentally, the same study showed that T S/A was not sensitive to the, sometimes extensive, calcium (Ca) and sodium (Na) concentration changes during the dialysis.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…The relationship between this metric and blood plasma potassium concentration suggested that the metric could actually measure outward potassium current. This hypothesis was confirmed by model studies and measurements on LQT2-patients [8]. Incidentally, the same study showed that T S/A was not sensitive to the, sometimes extensive, calcium (Ca) and sodium (Na) concentration changes during the dialysis.…”
Section: Introductionmentioning
confidence: 65%
“…Besides QT prolongation, classic ECG hallmark of hypokalemia is a reduced T-wave amplitude [6], while the opposite (hyperkalemia) is traditionally diagnosed as tall, peaked T-waves [7]. We recently proposed a metric to quantify the plasma potassium concentration [8], based on the ratio of down-going T-wave slope and T-wave amplitude (T S/A ) and tested it on patients undergoing haemodialysis. The relationship between this metric and blood plasma potassium concentration suggested that the metric could actually measure outward potassium current.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, an expansion using more anatomical models is crucial for further evaluation of the findings. In [3], a patient specific calibration is introduced to improve results on patient data. This substantiates a patient-dependency of at least their evaluated feature, but could also mean that a calibration is needed in general.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ECG as a continuous, non-invasive monitoring tool could shed a light on the relation between heart diseases and changes in the ionic concentration particularly after leaving the strictly supervised clinical area where dialysis takes place, i.e allowing a monitoring at home. Articles have been published showing that the reconstruction of extracellular K + concentration can be done using just one feature from the ECG with a quadratic regression [3]. In this study, we tried to estimate both K + and Ca 2+ concentrations from the ECG.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormalities in ventricular repolarization are reflected on the electrocardiogram (ECG) signal, in particular, on the T-wave morphology [5]. Different ECG biomarkers have been previously reported to be correlated with [K + ] levels, including the T-wave slope-to-amplitude ratio [6] or the T-wave right slope [7]. However, these biomarkers rely on specific local features of some parts the T-wave, but neglect the information contained in the whole T-wave morphology.…”
Section: Introductionmentioning
confidence: 99%